Acute Immune-Inflammatory Responses to a Single Bout of Aerobic Exercise in Smokers; The Effect of Smoking History and Status - Kastelein, Tegan Emma; Duffield, Rob; Marino, Frank E. (Frontiers in Immunology, 2015)
This study examined the acute immune and inflammatory responses to exercise in smokers compared to non-smokers, and further, the effect of smoking history on these immune-inflammatory responses. Fifty four recreationally active males who were either smokers (SM; n=27) or non-smokers (NS; n=27); were allocated into either young (YSM, YNS) or middle-aged groups (MSM, MNS) based on smoking status. Participants were matched for fitness and smoking habits and following familiarisation and baseline testing, undertook an exercise protocol that involved 40min of cycle ergometry at 50% of VO2peak. Venous blood was obtained pre and post (0min,1h, 4h) exercise to measure circulating leukocytes and inflammatory markers interleukin (IL)-6, IL-1β, IL-1ra and monocyte chemoattractant protein-1 (MCP-1). Compared to MNS, MSM showed elevated basal concentrations of MCP-1 which were increased with a longer smoking history (P<0.05). In response to exercise, YSM demonstrated an amplified IL-6 response from immediately- to 1h-post compared to YNS. Further, IL-1ra in YSM was elevated above that of YNS across all time points (P<0.05). The MSM group had higher IL-1β at baseline when compared to YSM, although IL-1ra was greater for YSM at baseline (P<0.05). Finally, the post-exercise leukocyte response was greater in MSM compared to YSM and non-smokers (P<0.05). In conclusion, smoker’s exhibit elevated MCP-1 and IL-1β which seems to be evident with a longer smoking history (~15years). Further, the differences in exercise-induced inflammatory responses noted in YSM may be indicative tobacco smoke exposure priming circulating leukocytes to amplify inflammatory responses.